1991
DOI: 10.1002/jcla.1860050406
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and long‐term liquid nitrogen storage of peripheral blood mononuclear cells for flow cytometry analysis effects on cell subset proportions and fluorescence intensity

Abstract: The effect of cryopreservation and long-term liquid nitrogen storage on peripheral blood mononuclear cell (PBMC) subsets was prospectively analyzed using monoclonal antibodies and flow cytometry. Brief cryopreservation did not significantly alter the proportion of positively stained cells for CD3+, CD4+, CD8+, CD14+, CD16+, and CD19+ cells. A small but statistically significant increase in the proportion of positive cells was observed for HLA-DR+ and HLe-1+ cells. Brief cryopreservation was associated with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…First of all, we verified that the CTV-PBMC bank, which is critical in this method, was sufficiently stable over time and did not vary when changing the bank. We demonstrated its stability over 509 days, making it easy to use over a long time, consistent with the literature showing storage stabilities of PBMC cryopreserved in liquid nitrogen for several years [ 12 ]. Therefore, a CTV-PBMC bank can be used to qualify several productions of MSC batches in the context of one clinical trial.…”
Section: Discussionsupporting
confidence: 88%
“…First of all, we verified that the CTV-PBMC bank, which is critical in this method, was sufficiently stable over time and did not vary when changing the bank. We demonstrated its stability over 509 days, making it easy to use over a long time, consistent with the literature showing storage stabilities of PBMC cryopreserved in liquid nitrogen for several years [ 12 ]. Therefore, a CTV-PBMC bank can be used to qualify several productions of MSC batches in the context of one clinical trial.…”
Section: Discussionsupporting
confidence: 88%
“…However, our new method was demonstrated to detect ADCC activity more sensitively than the Cr 51 -assay, with individual ADCC activities being measureable even when frozen PBMCs were used. On the other hand, the phenotype of frozen PBMCs was reportedly changed 21 22 , or minimally altered within 2 months after being frozen 23 24 . Indeed, Mata et al suggested that PBMCs thawed and left overnight had high ADCC activity, though a change in the NK phenotype was observed after overnight incubation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were placed in a cryo 1°C freezing container (Thermo Fisher Scientific, Rochester, NY) in a −80°C freezer for 24 hr and then transferred into a liquid nitrogen freezer until use. The PBMC were used within 2 months of the date they were frozen to minimize phenotypic changes induced by the length of cryopreservation (Tollerud et al, 1991; Seale et al, 2008). Frozen PBMC were thawed in a 37°C water bath until a small amount of frozen material was left, then washed in complete media.…”
Section: Methodsmentioning
confidence: 99%